2017
DOI: 10.1093/cercor/bhw379
|View full text |Cite
|
Sign up to set email alerts
|

Representational Similarity Mapping of Distributional Semantics in Left Inferior Frontal, Middle Temporal, and Motor Cortex

Abstract: Language comprehension engages a distributed network of frontotemporal, parietal, and sensorimotor regions, but it is still unclear how meaning of words and their semantic relationships are represented and processed within these regions and to which degrees lexico-semantic representations differ between regions and semantic types. We used fMRI and representational similarity analysis to relate word-elicited multivoxel patterns to semantic similarity between action and object words. In left inferior frontal (BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 96 publications
19
79
0
1
Order By: Relevance
“…The t-values associated with those correlations are indicated with shades of red and thresholded at p < 0.05, FDR corrected. Although expected for higher-order features (Freedman, Riesenhuber, Poggio, & Miller, 2001;Wagner, Paré-Blagoev, Clark, & Poldrack, 2001;Huth, Nishimoto, Vu, & Gallant, 2012;Carota, Kriegeskorte, Nili, & Pulvermüller, 2017), the widespread presence of low-level visual features within higher-order regions (see Table 1) appears to challenge a strict interpretation of the cortical visual hierarchy, which would predict results similar to what we observed for mid-level visual features.…”
Section: Figure 4 Seed Roi Weights and Feature-specific Informationasupporting
confidence: 59%
“…The t-values associated with those correlations are indicated with shades of red and thresholded at p < 0.05, FDR corrected. Although expected for higher-order features (Freedman, Riesenhuber, Poggio, & Miller, 2001;Wagner, Paré-Blagoev, Clark, & Poldrack, 2001;Huth, Nishimoto, Vu, & Gallant, 2012;Carota, Kriegeskorte, Nili, & Pulvermüller, 2017), the widespread presence of low-level visual features within higher-order regions (see Table 1) appears to challenge a strict interpretation of the cortical visual hierarchy, which would predict results similar to what we observed for mid-level visual features.…”
Section: Figure 4 Seed Roi Weights and Feature-specific Informationasupporting
confidence: 59%
“…Alternatively, considering that the comprehension of a word seems to be associated with activation of its articulatory motor program (Pulvermüller, 2005), the content of food-wasting and harmful scenarios might include words processed by overlapping regions in the motor area. It has been shown that action verbs and food nouns elicited similar brain response patterns in the left Inferior Frontal Gyrus and Motor Cortex (Carota, Kriegeskorte, Nili, & Pulvermüller, 2017) which overlap with our results. On the other hand, processing of food-wasting and harmful scenarios led to an increased activation in the left Amygdala and left dorsolateral Prefrontal Cortex, which are functionally connected during emotion regulation (Herwig et al, 2019), suggesting considerable emotional engagement during moral judgment of these scenarios.…”
Section: Discussionsupporting
confidence: 90%
“…This interpretation is in line with previous evidence that unprocessed foods tend to be perceived as more distant from edibility than processed foods that instead are perceived as ready to be consumed (Foroni et al, 2013). Both the inferior frontal and precentral gyri have also been found to represent food words as well as the corresponding action words associated with mouth and tools (Carota, Kriegeskorte, Nili, & Pulvermüller, 2017; see also De Lucia, Clarke & Murray, 2010 for environmental sounds). The results of the source estimation analysis failed to reveal any statistically significant differential activity in the OFC or in any other brain region associated with reward processing (i.e., ventromedial prefrontal cortex, striatum).…”
Section: Discussionsupporting
confidence: 88%